Factors Affecting the Quality of Life of Children with Thalassemia: Literature Review - Abida, Aisya Nur (Jurnal Biologi Tropis, 2024)
The chronic condition known as thalassaemia is a hereditary ailment that results in the loss or decreased synthesis of one or more globin chains in erythrocytes. Ineffective erythropoiesis, early erythrocyte breakdown, and anaemia are all possible outcomes of thalassaemia. In Indonesia, it is estimated that between 3-10% of people have β thalassaemia, whereas between 2.6-11% have α thalassaemia. Approximately 2,500 newborns are thought to be born with β-thalassemia major each year. The purpose of this study is to identify the variables that affect the quality of life for kids with thalassaemia so that the right kind of medication can be developed to lessen this issue. This study used the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) technique to conduct a literature review. The PubMed and ScienceDirect databases were used to conduct online searches for the literature. Three articles in all were chosen for examination based on search results that satisfied the inclusion requirements. The study findings from the three analysed publications indicate that the primary factor influencing a child's declining quality of life is school function. Children's age, the kind of iron chelation treatment, the frequency of transfusions, the number of family members with thalassaemia, and haematopoietic stem cell transplant operations are all factors that affect the quality of life of patients with thalassaemia. Based on the factors that influence the quality of life of children with thalassemia, the role of parents supported by the government and community is needed in the treatment of children with thalassemia.